Child-friendly family reduces parenting stress in Chinese families: the mediating role of family resilience - Chu, Amanda Man Ying; Tsang, Jenny Tsun Yee; Tiwari, Agnes; Yuk, Helina; So, Mike Ka Pui (Frontiers in Psychology, 2024)
The increasing prevalence of parenting stress has significant implications for the psychological well-being of both parents and children. In view of this, our study sought to examine the mediating and moderating role of family resilience in the association between child-friendly family and parenting stress. Our analysis involved a sample of 316 parents who dedicated a minimum of 14 hours per week to caring for their children. The parents were invited to complete three validated instruments-the parenting stress index short form (PSI), the family resilience assessment scale (FRAS), and inventory of the child-friendly family (ICF)-to evaluate their level of parenting stress, family resilience, and child-friendly family, respectively. We tested the mediation model by applying structural equation model analysis.It was found that child-friendly family negatively correlated with parenting stress (path coefficient = -0.56, p < .001). This relationship is mediated by family resilience. That is "childfriendly family" leads to increased "family resilience" (path coefficient = .68, p < .01), which in turn leads to lower "parenting stress" (path coefficient = -.30, p < .05). The mediation effect ratio was 26.70%. We used multiple regression analysis to test the moderation model and found that family resilience did not play a moderating role between child-friendly family and parenting stress. This study holds particular significance for two key reasons: Firstly, it elucidates the relationship between child-friendly family, family resilience, and parenting stress, highlighting the potential of creating a child-friendly family to reduce parenting stress through the enhancement of family resilience. Secondly, our findings provide valuable evidence for the development of innovative approaches that effectively and sustainably alleviate parenting stress.